2022
DOI: 10.1155/2022/7459139
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Efficiency of Nanohydroxyapatite on Repairing Type II Diabetes Dental Implant‐Bone Defect

Abstract: The purpose of this study was to see how a nanohydroxyapatite (n-HA) composite polyamide 66 (PA66) affected the repair of bone defects in diabetics with titanium implants, as well as to develop experimental materials for the creation of the interface between bone tissue and titanium implants. Rabbit bone marrow mesenchymal stem cells (MSCs) were isolated using n-HA/PA66 composite material, and the effect of coculture with the material on cell proliferation was analyzed after induction of mineralization. Bone d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%